2022
DOI: 10.1182/bloodadvances.2022007217
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the role of the immune microenvironment in multiple myeloma progression at a single-cell level

Abstract: Early alterations within the bone marrow microenvironment that contribute to the progression of multiple myeloma (MM) from its precursor stages could hold the key to identifying novel therapeutic approaches, yet the intrinsic variability in cellular populations between patients together with differences in sample processing and analysis methods have made it difficult to identify consistent changes between datasets. Here, we used single-cell RNA sequencing of BM cells from precursor stages, monoclonal gammopath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 54 publications
(67 reference statements)
3
19
0
Order By: Relevance
“…Prior studies already demonstrated the immunosuppressive state of BM microenvironment in MM patients, including exhaustion ( 49 , 50 ) and senescence ( 10 ) of T cells and increased Treg ( 13 ). However, we did not find significant difference on the proportion of CD8-COTL1 exhaustion T cell among MM groups and HDs, which is in line with the reports by Oksana Zavidij ( 22 ) and Carolina ( 51 ). Moreover, we did not observe the significant increase of PD1, LAG3, TIGIT, the classic immune checkpoints, on immune cells, which could help us to explain the reason of the unfavorable treatment efficacy of immune checkpoint inhibitors in MM clinic practices.…”
Section: Discussionsupporting
confidence: 92%
“…Prior studies already demonstrated the immunosuppressive state of BM microenvironment in MM patients, including exhaustion ( 49 , 50 ) and senescence ( 10 ) of T cells and increased Treg ( 13 ). However, we did not find significant difference on the proportion of CD8-COTL1 exhaustion T cell among MM groups and HDs, which is in line with the reports by Oksana Zavidij ( 22 ) and Carolina ( 51 ). Moreover, we did not observe the significant increase of PD1, LAG3, TIGIT, the classic immune checkpoints, on immune cells, which could help us to explain the reason of the unfavorable treatment efficacy of immune checkpoint inhibitors in MM clinic practices.…”
Section: Discussionsupporting
confidence: 92%
“…The monocyte/MP subset was significantly enriched in the BM of patients with PC disorders other than in healthy donors (Figure 1C). Although the monocyte/MP population has been reported to be enriched in the BM microenvironment in MM rather than in precancerous-stage MGUS, 21,[24][25][26] we observed a higher proportion of the monocyte/MP population in the MGUS stage than in the NDMM stage (Figure 1C,D and Figure S1). When compared to NDMMs, we identified a relative increase of monocyte/MPs in RRMMs (Figure 1C-E and Figure S1), which indicated the potential contribution of monocytes/MPs to disease relapse/ refractoriness.…”
Section: Compositional Immune Cell Alterations Exist In the Whole Pro...mentioning
confidence: 60%
“…Furthermore, including additional risk factors for biomarker-defined MM patients would improve the identification of patients with a high probability of rapid progression to active myeloma and could facilitate treatment decisions in these patients, an opinion which is shared by Akhlaghi et al. 21 Combining the existing criteria with risk factors such as cytogenetic factors, 4 light chain proteinuria, 24 gene expression data, 5 , 28 circulating plasma cells, 29 whole exome 30 or genome, 31 and immune 32 profiling, among others, should increase the prognostic accuracy of biomarker-defined MM. Very recent studies suggest to adapt the definition of patients with a high FLCratio and to include the detection of concomittant proteinuria (>200 mg/24 h) as an essential criterion for high-risk in those patients.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the natural history of truly smoldering and biomarker-defined MM should be prospectively studied using modern diagnostic criteria as envisaged in the CARRISMM study, 35 and therapeutic studies in these patients should include a carefully followed untreated control group with one of the endpoints being overall survival. 32 , 36 …”
Section: Discussionmentioning
confidence: 99%